Alokasi Zakat sebagai Alternatif Biaya Pendidikan di Masjid Darussalam Permata Biru Cinunuk, Kota Bandung - Iwan Sopwandin (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2019)
This research aims at investigating the role of zakat as an alternative means to fund education. Zakat is God’s command with dual functions, as a means of worship and social responsibility. Zakat could be spent to fund activities for the purpose of following Allah’s path (fi sabilillah). Yusuf Qardawi argues that ‘fi sabilillah’ is a form of jihad in the way of Allah. Whereas jihad in this sense covers struggle for education (tarbawi). This study utilizes Tafsir Ilmy approach to understand the interpretation of zakat for educational fund, while then enrich the data through a qualitative research. The data was gathered using observation, interviews, and documentation. The study begins by examining the interpretation of the Qur’an shura At Taubah (9): 60 according to a number of muffasirs and used it as the bedrock to analyse how zakat could become an alternative source for fund in education implemented in Masjid Darussalam Permatabiru Cinunuk. The research found that in Darussalam mosque, zakat function as scholarship fund namely Darussalam Scholarship (Dharso) which was given to four students to account for their study at university.